RISK FACTOR PREVALENCE AND PROBABILITY OF FATAL CARDIOVASCULAR EVENTS IN MEN 42-44 YEARS OLD - A. A. Aleksandrov; V. B. Rozanov; Е. Yu. Zvolinskaya; Kh. S. Pugoeva (Кардиоваскулярная терапия и профилактика)
Aim. To evaluate  prevalence  of the  main risk factors  (RF) and  fatal outcome probability of cardiovascular diseases (CVD) in 10 years among men 42-44 years old.Material and methods. Totally, 303 men studied at the age 42-44 y.o., under  the  ordinary step  of 32-year  lasting prospective  cohort  study. Response on invitation for investigation was 30,1%. Subjects underwent standardized   questionnaire;  triple blood  pressure  measurement, as pulse, length and mass of body; thickness of adipose layers over triceps, scapula and abdominal wall measurement; waist and hip circumference; measurement of total and  high density  lipoproteides  cholesterol,  as triglycerides and blood glucose.  Statistics was done via software IBM SPSS Statistics 22.Results. The characteristics of the studied group is presented as simple descriptive statistics. At the moment of study, 23% of men had elevated blood pressure, mostly at the level of arterial hypertension (AH) grade 1 (14,5%). There was anamnesis  of AH in 44,6% participants  and 27,1% take antihypertensive medication, but just 8,9% do treat actively. Overweight and obesity were found in 67% of the studied.  Abdominal obesity was found in 87 (28,7%). More than 40% of them smoke. In 42,6% of men there  were significant proatherogenic changes  in serum found. Low physical activity was set for 26,1% of the studied. 65% of men from this group have 2 and more risk factors. It is stated that most of the men (90%) have moderate  risk of fatal CVD development next 10 years,  by SCORE, and just 8,9% have low estimated  risk. The main impact on the overall risk have cholesterol (47,6%) and smoking (33,7%).Conclusion. High rate of the main RF for CVD in men 42-44 y.o. and moderate probability of fatal CVD for the next 10 years strictly dictate on the necessity  of individualized active prevention of CVD with the main direction towards positive motivation for healthy life style — cessation of bad  habits,  especially smoking, rational food intake, physical activity optimization,  atherogenic   lipid profile  correction  and  effective  AH treatment.